2020
DOI: 10.1016/j.jaci.2019.12.296
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gut Microbiota and Chronic Spontaneous Urticaria

Abstract: This study evaluated the effectiveness, proper dosage and possible response of OMALIZUMAB (Biologics) for Chronic Idiopathic Urticaria (CIU) patients in KSA with antihistamine refractory CIU disease related quality of life. METHODS: The study was prospective and descriptive in nature. Omalizumab was used in those patients who did not respond to up dosing of Antihistamine, steroids and cyclosporine. Omalizumab is recombinant humanized monoclonal antibody against human IgE and has good safety profile due to biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CSU Patients (n = 13) UAS score Mild (7)(8)(9)(10)(11)(12)(13)(14)(15) 1 (8%) Moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 6 (46%) Severe (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) 6 (46%)…”
Section: Variableunclassified
See 1 more Smart Citation
“…CSU Patients (n = 13) UAS score Mild (7)(8)(9)(10)(11)(12)(13)(14)(15) 1 (8%) Moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 6 (46%) Severe (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) 6 (46%)…”
Section: Variableunclassified
“…Autoimmunity type I (IgE autoantibodies to IL-24, thyroperoxidase, double-stranded DNA, and other autoallergens) or type IIb (IgG antibodies to the patient's own IgE or its high-affinity receptor-FcεRI) are involved in a large proportion of CSU cases [8], but also other factors have been elucidated: infections, pseudoallergic reactions, coagulation, stress, vitamin D [9]. Several recent studies have been identified altered gut microbiota as a possible underlying cause of CSU [6,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal microbiota provides a vast and continuous stimulation for the immune system. Chronic spontaneous urticaria seems to be associated with low-level systemic or intestinal inflammation (7,8).…”
mentioning
confidence: 99%
“…The gut microbiota of patients with chronic spontaneous urticaria and healthy individuals were obtained by 16s rRNA massive sequencing.In this review, we discuss the different factors that can exacerbate established chronic spontaneous urticaria, prolong the duration of the condition and encourage the need for second and third line therapy.However, about 50% of patients are resistant to second-generation nonsedating H1-antihistamines, and the precise pathogenesis remains largely unknown but seems to be associated with low-level systemic or intestinal inflammation(6).The gastrointestinal microbiota provides a vast and continuous stimulation for the immune system. Chronic spontaneous urticaria seems to be associated with low-level systemic or intestinal inflammation(7,8).Intestinal permeability was reported to be increased in chronic spontaneous urticaria and this was partly reversed by 24 days on a reduced pseudoallergen diet.Increasing evidence suggests that the gut microbiome plays a role in the pathogenesis of allergy and autoimmunity(9).…”
mentioning
confidence: 99%